The Histological Structure Of The Crop (Ingluvies) In Poultry - Zainuddin Z; Dian Masyitha; Yusni Mulyana; Fitriani F (Universitas Syiah Kuala, 2014)
This research aims to see the histological structure of the crop in poultry. Animals used were chicken (Gallus domesticus), duck (Anser anserdomesticus), and pigeon (Columba domesticus) each group consists of three animals. Crop tissue of each animal were taken and processed inmicrotechnic and stained with Hematoxilin and Eosin (HE), then observed with digital microscope. The results showed that there were thesimilarity of the general structures of crop from the three types of these poultry. which consists of the tunica mucosa, tuni ca submucosa, tunicamuscularis and tunica serosa. Lamina muscularis in duck is more obvious than chicken and pigeon. Mucosal gland of duck shaped oval, chickenshaped rounded, and the pigeons are not found. Tunica muscularis duck arranged longitudinally in the outside dan ci rcular in the inside. Tunicamuscularis duck arranged longitudinally in the inside, and circular in the outside, and tunica muscularis in pigeon just arranged longitudinally.____________________________________________________________________________________________________________________Key words: histological, crop, poultry